2018
DOI: 10.1007/s11673-018-9881-6
|View full text |Cite
|
Sign up to set email alerts
|

Should Gender Reassignment Surgery be Publicly Funded?

Abstract: Transgender people have among the highest rates of suicide attempts of any group in society, driven strongly by the perception that they do not belong in the sex of their physical body. Gender reassignment surgery (GRS) is a procedure that can change the transgender person’s physical body to accord with their gender identity. The procedure raises important ethical and distributive justice concerns, given the controversy of whether it is a cosmetic or medical procedure and the economic costs associated with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It has seemed to many, such as Bracanovic [1] and Go [12] (p528), that rights to GAH can only be grounded in rights to harm or illness mitigation or cure. This conclusion is at odds with the views of our rights to GAH articulated by trans theorists, authors, and activists.…”
Section: VIImentioning
confidence: 99%
See 2 more Smart Citations
“…It has seemed to many, such as Bracanovic [1] and Go [12] (p528), that rights to GAH can only be grounded in rights to harm or illness mitigation or cure. This conclusion is at odds with the views of our rights to GAH articulated by trans theorists, authors, and activists.…”
Section: VIImentioning
confidence: 99%
“…A second natural way of grounding rights to GAH is in rights to have the harm one is experiencing mitigated: trans and non-binary people have very high rates of suicide and severe depression and GAH mitigates this depression. [2,12] (pp26-28). However, many trans people are not depressed or suicidal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 In the United Kingdom, arguments to publicly fund GAS via the National Health Service are based on clinical necessity, cost-effectiveness, justice, and ethical consistency. 14 Among GAS procedures, FFS can be more effective at relieving GD than genital surgery (because patients tend to focus more on the appearance of their faces than their genitals), while also protecting patients from violence and discrimination due to their physical appearance. 12 The importance of FFS may increase during a pandemic in which the widespread use of masks prevents others from seeing the nose and mouth, which can be made to appear more feminine with makeup.…”
Section: Case Presentationmentioning
confidence: 99%
“…A recent study found significantly reduced risk of mental health treatment in TGNC patients after receiving GAS but not HRT alone 13 . In the United Kingdom, arguments to publicly fund GAS via the National Health Service are based on clinical necessity, cost‐effectiveness, justice, and ethical consistency 14 . Among GAS procedures, FFS can be more effective at relieving GD than genital surgery (because patients tend to focus more on the appearance of their faces than their genitals), while also protecting patients from violence and discrimination due to their physical appearance 12 .…”
Section: Case Presentationmentioning
confidence: 99%